Meningkatkan Hasil Belajar Akidah Akhlak Melalui Metode Demonstrasi Pada Siswa Kelas II Madrasah Ibtidaiyah Amanah - Kholidah, Nur (MGMP PAI SMP BINTAN, 2023)
The educational process is expected to touch students' understanding in receiving the lessons delivered by the teacher. Likewise, the efforts made by the moral aqidah teacher at MI Amanah Kandis, Siak Regency City, apply various learning methods in order to improve the learning outcomes of class II students. This research aims to describe the increase in the ability to apply and emulate the characteristics of Asmaul Husna in moral aqidah lessons through the demonstration method for class II students at MI Amanah Kandis Kota. This research is classroom action research with 17 class II MI Amanah students as research subjects. The results of data analysis show that the percentage level of student learning outcomes increased after action using the demonstration method. So it does not rule out the possibility of further research being carried out at a later date by other educators.